On the trail of the Poets of the Great War : Robert Graves & Siegfried Sassoon - McPhail, Helen (Battleground Europe. On the trail of the poets of the Great War., 2001)
The war memoirs of these two officers with the Royal Welsh Fusiliers have never been out of print since their first publication. Both men won instant and enduring fame with these very different narratives, which made them two of the most influential participants in shaping later attitudes to the war. Graves gave offence in many quarters with his factual inaccuracies and/or slurs on various units of the British Army. Sassoon's nostalgic evocation of his cricketing and fox-hunting background contrast with the detailed narrative of personalities and life in the Battle of the Somme and the Battle.